Star in the forest - Resau, Laura (New York : Yearling, 2012)
After eleven-year-old Zitlally's father is deported to Mexico, she takes refuge in her trailer park's forest of rusted car parts, where she befriends a spunky neighbor and finds a stray dog that she nurses back to health and believes she must keep safe so that her father will return.
"A Yearling book.".
Wilson's Children, October 2010.
School Library Journal starred, February 2010.
Booklist starred, February 2010.
Horn Book, October 2010.
Bulletin (Center for Children's books), May 2010.
Keywords: Illegal aliens -- Juvenile fiction; Fathers -- Juvenile fiction; Trailer camps -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Illegal aliens -- Fiction; Fathers -- Fiction; Trailer camps -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction; Illegal aliens -- Fiction; Fathers -- Fiction; Trailer parks -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction; Illegal aliens -- Fiction; Fathers -- Fiction; Trailer camps -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction